A pose-based structural dynamic model updating method for serial modular robots. (15th February 2017) - Mohamed, Richard Phillip; Xi, Fengfeng (Jeff); Chen, Tianyan
Abstract: A new approach is presented for updating the structural dynamic component models of serial modular robots using experimental data from component tests such that the updated model of the entire robot assembly can provide accurate results in any pose. To accomplish this, a test-analysis component mode synthesis (CMS) model with fixed-free component boundaries is implemented to directly compare measured frequency response functions (FRFs) from vibration experiments of individual modules. The experimental boundary conditions are made to emulate module connection interfaces and can enable individual joint and link modules to be tested in arbitrary poses. By doing so, changes in the joint dynamics can be observed and more FRF data points can be obtained from experiments to be used in the updating process. Because this process yields an overdetermined system of equations, a direct search method with nonlinear constraints on the resonances and antiresonances is used to update the FRFs of the analytical component models. The effectiveness of the method is demonstrated with experimental case studies on an adjustable modular linkage system. Overall, the method can enable virtual testing of modular robot systems without the need to perform further testing on entire assemblies. Highlights: A new model updating approach for serial modular robots was developed. Experimental component testing method to match connection interface conditions. Tests are carried out for multiple joint module positions to check for position-based structural dynamic dependencies. Solution of overdetermined model updating problem is found using a direct search method. Results show that the updated component models can provide accurate results for a serial modular robot assembly in any position.